Asuhan Keperawatan Pada Ibu Hamil Dengan Masalah Keperawatan Neusea Dengan Penerapan Perasan Jeruk Nipis Air Hangat Dan Madu Di Puskesmas Gedong Tataan - Desmarita Desmarita; Surmiasih Surmiasih; Riska Hediya Putri (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Nausea and vomiting during pregnancy are common complaints, particularly in the first trimester, and can lead to nutritional imbalance as well as a decreased quality of life. Natural substances such as lime, honey, and warm water are known to contain bioactive compounds that can reduce nausea symptoms through mechanisms including increased gastric motility, soothing the gastrointestinal mucosa, and stabilizing gastric pH. This study aims to describe nursing care for pregnant women with nausea through the application of a complementary therapy using warm lime juice and honey. The study employed a case study design involving two pregnant women experiencing nausea and vomiting at Gedong Tataan Health Center. The nursing process included assessment, nursing diagnosis formulation (nausea, disturbed sleep pattern, and discomfort), planning, implementation, and evaluation. The intervention consisted of consuming a mixture of 30 ml lime juice, 1 tablespoon of honey, and 250 ml of warm water for three consecutive days before breakfast. The evaluation results indicated a reduction in the frequency of nausea, decreased sensation of wanting to vomit, improved appetite, and better sleep quality. Both patients showed positive responses, and no side effects were observed. It is recommended that pregnant women may use warm lime juice and honey as an alternative therapy to alleviate nausea during pregnancy.